The Evolution of Data-Oriented Services systems adapt quickly with XML and web services. - Zager, Matthew
My colleague wrote an article for XML-J two years ago about an opportunity we had to solve our data management challenges with XML ("Managing Data sources with XSLT,". The result of our work was our XML Data Services (XDS), an XML data access language and processing engine, which allowed us to quickly and easily manage the bi-directional transform between data sources and XML. A couple years have passed and new challenges have arisen and been solved by leveraging our XML data access engine and Web services.